Formal guidelines from an expert panel: intensive care unit medical staffing, organisation and working hours to improve quality of life at work in France - Nicolas Terzi; Guillaume Thiery; Nicolas Bèle; Naike Bigé; David Brossier; Alexandre Boyer; Edouard Couty; Laëtitia Flender; Cyril Manzon; Jean-Paul Mira; Sofia Ortuno; Vincent Peigne; et al. (Annals of Intensive Care)
Abstract Background Intensive care units (ICU) are characterized by high medical assistance costs and great complexity. Recommendations to determine the needs of medical staff are scarce, generating appreciable variability. The French Intensive Care Society (FICS) and the French National Council of Intensive Care Medicine (CNP MIR, Conseil National Professionel de Médecine Intensive Réanimation) have established a technical committee of experts, the purposes of which were to draft recommendations regarding staffing needs in ICUs and to propose optimal organisation of work hours, a key objective being improved workplace quality of life. Results Literature analysis was conducted according to the GRADE methodology (Grade of Recommendation Assessment, Development and Evaluation). The synthesis work of the experts according to the GRADE method led to the development of 22 recommendations in 6 field. The experts issued a strong recommendation associated with a high level of evidence which is that work organization be given priority during periods of permanent care, with a maximum 16 h of consecutive work permitted. For 21 other recommendations, the level of evidence did not allow GRADE classification, and led to the formulation of expert opinions. All recommendations and expert opinions were validated (strong agreement). Conclusion The work in the intensive care unit and in the intermediate intensive care unit is multifaceted, both clinical and non-clinical, and must include at least the following continuity and quality for patient safety. This document provides a detailed framework to propose an optimal medical staff.